KEYNOTE-022: Pembrolizumab with trametinib in patients with BRAF wild-type melanoma or advanced solid tumours irrespective of BRAF mutation. (January 2022) - Maio, Michele; Carlino, Matteo S.; Joshua, Anthony M.; McWhirter, Elaine; Ribas, Antoni; Ascierto, Paolo A.; Miller, Wilson H.; Butler, Marcus O.; Ferrucci, Pier Francesco; Zielinski, Robert R.; Del Vecchio, Michele; Gasal, Eduard; et al.
Abstract: Objectives: Parts 4 and 5 of the phase 1/2 KEYNOTE-022 study investigated the maximum tolerated dose (MTD), safety,  and efficacy of pembrolizumab plus trametinib in solid tumours and BRAF wild-type melanoma. Patients and methods: Patients received intermittent or concurrent dosing of pembrolizumab plus trametinib. Concurrent dosing was 2 or 4 weeks of trametinib run-in followed by concurrent pembrolizumab every 3 weeks (Q3W) plus trametinib once daily (QD). Intermittent dosing was 2 weeks of trametinib run-in followed by pembrolizumab plus intermittent trametinib (1 week off/2 weeks on). A 3 + 3 dose escalation was used, followed by dose confirmation. Results: Forty-two patients were enrolled. No dose-limiting toxicities (DLTs) occurred at initial dose levels (DL). At subsequent DLs, 10 of 38 evaluable patients had DLTs. For concurrent dosing, MTD was pembrolizumab 200 mg Q3W plus trametinib 1.5 mg QD, with a 2-week trametinib 1.5 mg QD run-in (concurrent DL2a); in concurrent DL2a group, five (31%) patients had grade 3/4 treatment-related adverse events (TRAEs); the objective response rate (ORR) was 0%. ORR was 40% in concurrent DL1 and 0% in concurrent DL2b. For intermittent dosing, MTD was pembrolizumab 200 mg Q3W plus trametinib 2 mg QD with a 2-week trametinib 2 mg QD run-in (intermittent DL2); in the intermittent DL2 group, seven (47%) patients had grade 3/4 TRAEs; ORR was 27%. ORR in intermittent DL1 was 33%. Conclusions: MTDs for concurrent and intermittent dosing of pembrolizumab with trametinib were identified. The combination had limited antitumour activity, numerically higher ORR with intermittent versus concurrent dosing, and manageable safety. ClinicalTrials.gov identifier: NCT02130466 . Highlights: Pembrolizumab plus trametinib was investigated in parts 4 and 5 of KEYNOTE-022. Patients in parts 4 and 5 had BRAF wild-type melanoma or solid tumours. Maximum tolerated doses were identified for concurrent and intermittent dosing. The safety profile of pembrolizumab plus trametinib was manageable. Limited antitumour activity was observed; further investigation is warranted.